La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Emotions and social movements - Flam, Helena; King, Debra (Routledge, 2005)
Addressing issues of emotion in social movements, this internationally oriented volume will appeal to both sociologists and political activists given its broad approach and unique emphasis on emotions in protest, dissent and social movements.
Keywords: 1900-1999; care; discipline; militance; mouvements sociaux; outils; ouvrages de références; périodes historiques; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
https://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1284&context=jgspl
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis